Impact of the COVID-19 Pandemic on Breast Cancer Management in Portugal - Alpuim Costa, Diogo (2022)
Funding Information: We would like to thank Andrea Bothwell who wrote the manuscript outline and first draft on behalf of Springer Healthcare Communications. We also thank Prof. Carina Silva (ESTEsL – Escola Superior de Tecnologias de Saúde de Lisboa) who performed the preliminary statistical analysis of this study. This medical writing assistance and statistical analysis was funded by CUF Oncologia. Funding Information: Diogo Alpuim Costa has received honoraria from the Portuguese Navy, CUF Oncologia, and NTT DATA, and has served as a speaker, advisory board member, or has received research or education funding from CUF Oncologia, AstraZeneca, Hoffmann-La Roche, Merck KGaA, Novartis, Pfizer, Uriage, Daiichi Sankyo, Gilead, Merck Sharp & Dohme, Nanobiotix, Puma Biotechnology Inc., Sanofi, and Seagen Inc. Margarida Brito has participated as advisory board member for Roche, Novartis, Merck Sharp & Dohme, and Pfizer. Mário Fontes-Sousa has served as a speaker or advisory board member for Bristol Myers Squibb, Daiichi Sankyo, Gilead, Lilly, Merck Sharp & Dohme, Novartis, Pfizer, Roche, and Servier. Diogo Martins-Branco received honoraria and advisory board fees from Janssen, Pfizer, Merck Sharp & Dohme, Angelini, AstraZeneca, and Novartis, meeting and travel grants from LEO Farmacêuticos, Merck Sharp & Dohme, Ipsen, Janssen, and Roche, and institutional grants from F. Hoffmann-La Roche Ltd. José Guilherme Gonçalves Nobre, João Paulo Fernandes, Marta Vaz Batista, Ana Simas, Carolina Sales, Helena Gouveia, Leonor Abreu Ribeiro, Andreia Coelho, Mariana Inácio, André Cruz, Mónica Mariano, Joana Savva-Bordalo, Ricardo Fernandes, André Oliveira, Andreia Chaves, Mafalda Sampaio-Alves, and Noémia Afonso have nothing to declare. Publisher Copyright: © 2022, The Author(s).